Coulman High VSP, Antarctica, 2010 - Bruce Luyendyk; Frank Rack (International Federation of Digital Seismograph Networks, 2011)
Goals: The seismic experiments will be designed to obtain better estimates of seismic velocities at drill site CH-1 (-77.465971, 171.581693) beyond those obtained in the MCS survey. Better velocities will enable informed decisions about drilling depths and whether to use the Fast Drill or Reentry method to reach the CHMU and below